2016
DOI: 10.1590/1518-8345.0547.2698
|View full text |Cite
|
Sign up to set email alerts
|

Complications of central venous catheter in patients transplanted with hematopoietic stem cells in a specialized service

Abstract: Objective: to identify the model, average length of stay on site and complications of central venous catheter in patients undergoing transplant of hematopoietic stem cells and verify the corresponding relationship between the variables: age, gender, medical diagnosis, type of transplant, implanted catheter and insertion site. Method: a retrospective and quantitative study with a sample of 188 patients transplanted records between 2007 and 2011. Results: the majority of patients used Hickman catheter with an av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Another study involving 50,000 patients on intravenous therapy confirmed that loss of permeability of the catheter is responsible for the largest number of interruptions in intravenous therapy, accounting for 43% of incidents (20) . On the other hand, other researchers, who assessed the complications of CVCs in patients transplanted with HSC in a specialized service, concluded that fever/bacteremia was the most present complication (7) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study involving 50,000 patients on intravenous therapy confirmed that loss of permeability of the catheter is responsible for the largest number of interruptions in intravenous therapy, accounting for 43% of incidents (20) . On the other hand, other researchers, who assessed the complications of CVCs in patients transplanted with HSC in a specialized service, concluded that fever/bacteremia was the most present complication (7) .…”
Section: Discussionmentioning
confidence: 99%
“…Considering the venous fragility caused by HSCT or by the patient's initial disease and due to the need for simultaneous infusion of incompatible solutions and for adequate parenteral treatment, a CVC is essential (6)(7) . The Hickman® long-term central venous catheter (LTCVC) has been extensively used in HSCT units.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the complications related to CVC insertion site, the literature states that internal jugular, subclavian, and femoral vein catheters are more vulnerable to embolisms and hemorrhage; the jugular and subclavian veins are safer in terms of bacterial contamination, but susceptible to risk of pneumothorax, hemothorax, and air embolisms; and the femoral vein is less recommended due to greater incidence of bacterial infection and thrombosis, in addition to limiting patient movement (22) . Secondary dressings are indicated in specific situations, which can justify the lower overall frequency and greater usage in femoral accesses.…”
Section: Discussionmentioning
confidence: 99%
“…Combined strategies aimed at CVC care can increase collaboration among professionals in the ICU, the institution and even other centers (8,(20)(21)(22)(23) .…”
Section: Discussionmentioning
confidence: 99%